Quadriceps Muscle Fatigue Reduces Extension and Flexion Power During Maximal Cycling - O'Bryan, Steven J.; Taylor, Janet L.; D'Amico, Jessica M.; Rouffet, David M. (Frontiers in Sports and Active Living, 2022)
Purpose: To investigate how quadriceps muscle fatigue affects power production over the extension and flexion phases and muscle activation during maximal cycling. Methods: Ten participants performed 10-s maximal cycling efforts without fatigue and after 120 bilateral maximal concentric contractions of the quadriceps muscles. Extension power, flexion power and electromyographic (EMG) activity were compared between maximal cycling exercises. We also investigated the associations between changes in quadriceps force during isometric maximal voluntary contractions (IMVC) and power output (flexion and extension) during maximal cycling, in addition to inter-individual variability in muscle activation and pedal force profiles. Results: Quadriceps IMVC (-52 ± 21%, P = 0.002), voluntary activation (-24 ± 14%, P < 0.001) and resting twitch amplitude (-45 ± 19%, P = 0.002) were reduced following the fatiguing task, whereas vastus lateralis (P = 0.58) and vastus medialis (P = 0.15) M-wave amplitudes were unchanged. The reductions in extension power (-15 ± 8%, P < 0.001) and flexion power (-24 ± 18%, P < 0.001) recorded during maximal cycling with fatigue of the quadriceps were dissociated from the decreases in quadriceps IMVC. Peak EMG decreased across all muscles while inter-individual variability in pedal force and EMG profiles increased during maximal cycling with quadriceps fatigue. Conclusion: Quadriceps fatigue decreases power production during the extension and flexion phases of maximal cycling. The dissociation between quadriceps fatigue and power reduction likely resulted from decreased activation of all lower-limb muscles and increased inter-individual variability in the motor control pattern.